2018
DOI: 10.1016/j.yjmcc.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ca2+ signaling by acute hypoxia and acidosis in rat neonatal cardiomyocytes

Abstract: Our studies suggest that acute hypoxia suppresses I in rapidly inactivating cell population by a mechanism involving Ca-dependent inactivation, while compromised mitochondrial Ca uptake seems also to contribute to I suppression in slowly inactivating cell population. Proximity of cellular Ca pools to sarcolemmal Ca channels may contribute to the variability of inactivation kinetics of I in the two cell populations, while acidosis suppression of I appears mediated by proton-induced block of the calcium channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 67 publications
(77 reference statements)
7
8
0
Order By: Relevance
“…While the suppressive effects of hypoxia on I Ca depended critically on the cell type expressing slowly or rapidly inactivating Ca 2+ channels, acidosis effects were independent of cell types. The stronger suppressive effects of hypoxia on slowly inactivating I Ca cells was consistent with the idea that Ca 2+ dependent inactivation protects the channel against hypoxic suppression (scheme 1), somewhat similar to that found in adult and neonatal rat cardiomyocytes where suppression of CDI by Ba 2+ [17][18][19], or Ca 2+ over-buffering [19] enhanced the hypoxia's suppressive effects. Unexpectedly, hypoxia was more effective in suppressing Ca 2+ signaling measured at the RyR2 micro-domains rather than in global cytosolic space, suggesting variable effects of hypoxia on calcium signaling pathway.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…While the suppressive effects of hypoxia on I Ca depended critically on the cell type expressing slowly or rapidly inactivating Ca 2+ channels, acidosis effects were independent of cell types. The stronger suppressive effects of hypoxia on slowly inactivating I Ca cells was consistent with the idea that Ca 2+ dependent inactivation protects the channel against hypoxic suppression (scheme 1), somewhat similar to that found in adult and neonatal rat cardiomyocytes where suppression of CDI by Ba 2+ [17][18][19], or Ca 2+ over-buffering [19] enhanced the hypoxia's suppressive effects. Unexpectedly, hypoxia was more effective in suppressing Ca 2+ signaling measured at the RyR2 micro-domains rather than in global cytosolic space, suggesting variable effects of hypoxia on calcium signaling pathway.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, we conclude that PKA-mediated phosphorylation does not protect the channel against the suppressive effects of hypoxia in hiPSC-CMs. These results are consistent with those reported in adult rat cardiomyocytes [17,18] or in rN-CMs [19] and contrasts sharply with those described for adult guinea pig cardiomyocytes [36].…”
Section: B Hypoxia Effects On Ba 2+supporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, using genetically engineered mitochondria-targeted Ca 2+ biosensors, several groups clearly showed that spontaneous beating promotes beat-tobeat mitochondrial Ca 2+ uptake in neonatal cardiomyocytes [14,28]. Moreover, Morad's group also showed that mitochondrial Ca 2+ buffering influences the activity of voltage-gated L-type Ca 2+ channel at the plasma membrane in neonatal cardiomyocytes [127]. Quantitative and simultaneous measurements of cytosolic Ca 2+ and mitochondrial Ca 2+ kinetics combined with appropriate genetic modification of MCU complex activity will help elucidate the contribution of mitochondrial Ca 2+ handing to the formation of Ca 2+ transient in each type of cardiomyocytes.…”
Section: Handling In Cardiomyocytesmentioning
confidence: 99%